The Phenomenon of Sudden Tourism: Access Legibility of Tlocor Marine Tourism and Its Sustainability - Avenzoar, Azkia; Mutia, Fairuz; Sunarya, Wendy (Institut Teknologi Adhi Tama Surabaya, 2024)
Tourism potential is not only present because of the right planning but can also come suddenly (sudden tourism). This condition is what happened in the Jabon - Sidoarjo area. The Sidoarjo mud disaster that has occurred since 2006 has resulted in several regional tourism potentials, some of which have developed. The effort to develop tourism potential based on locality requires harmony between the residential environment that has been formed and the tourist attractions that have recently emerged. This research was conducted on the acces road heading to Tlocor Marine Tourism. The method used in this research is a descriptive analityc method with a focus on the access legibility. This method is used to observe and analyze district development patterns by local government regulations that are synchronized with access legibility theory. The results showed that tourism potential must be supported by physical and non-physical aspects. For this reason, a strategy is needed to elaborate between the tourism potential that emerged later with the settlements and cultural spaces that emerged later.